A Tale of Two (?) Cities : Lisbon and Almaraz at the Dawn of the Iron Age - Sousa, Elisa de (2019)
During the last two decades, archaeological data concerning the Iron Age occupation of the two main settlements located in the Tagus estuary, the hill of Castelo de São Jorge (Lisbon) and Quinta do Almaraz (Almada) has strongly increase. Their close geographical proximity, along with the strong Phoenician presence attested in both sites, since at least the late eighth-early seventh century BCE, are elements that allow us to revisit the available data in order to better understand the links that connected these important locations during the so-called "Orientalizing" period. This article presents and argues the hypothesis that both settlements were, in fact, part of a single political-administrative cell, which was the main base of the Phoenician presence in the Tagus estuary. This new approach enables a more comprehensive reading concerning the impact and strategies of Phoenician colonization along the Iberian western Atlantic shores.